The Influence of Monetary Policy and Economic Factors on Employment Opportunities in ASEAN 6 Countries - Ningsih, Putri Ayu; Setyowati, Eni; Hasmarini, Maulidyah Indira; Purnomo, Didit (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this research was to determine the influence of monetary policy (interest rates and inflation) and economic factors (foreign direct investment and domestic product growth) on employment opportunities in ASEAN-6 countries. In this research using Quantitative Research Methods, the regression used is panel data regression with a random effect model using Eviews-10 software. This research shows that monetary policy (interest rates and inflation) and economic factors (foreign direct investment and domestic product growth) jointly influence employment opportunities. Individually, monetary policy (interest rates and inflation) does not affect employment opportunities. Meanwhile, the economic factors explained by foreign investment have a positive and significant influence on employment opportunities, while the growth of domestic products has a negative and significant influence on employment opportunities.